What motivates employees to participate in continuous improvement activities?. (10th November 2017) - Jurburg, D.; Viles, E.; Tanco, M.; Mateo, R.
Abstract : Continuous improvement (CI) is still one of the strongest ways for companies to achieve process excellence in order to survive in nowadays' competitive environments. Yet, it is still very difficult to implement and sustain CI systems, mainly because of the difficulty in engaging people in these activities. Based on an exhaustive literature review, followed by a three-round Delphi study with Spanish experts, this paper helps to assess what the main elements are with respect to the CI system that could motivate employees' intention to participate in CI activities. Main results show 44 elements grouped into 10 factors that could affect employees' intention to participate. These factors were structured into a more comprehensive model following an interpretive structural modelling approach.